Viral load change and time to death among adult HIV/AIDS patients on ART after test-and-treat in Northwest Ethiopia: a retrospective multi-center follow-up study using Bayesian joint modeling - Abeje, Eyob Tilahun; Agedew, Eskezyiaw; Endalew, Bekalu; Alen, Gedefaw Diress (Frontiers in Public Health, 2025)
IntroductionAmong patients infected with Human Immunodeficiency Virus who are on antiretroviral therapy, nearly one-fifth develop viral load rebound within 2 years of initiation of therapy. Studies on viral load change are limited in Ethiopia. Previous studies have not adequately accounted the undetectable viral load in the analysis and the association between viral load change and time to death. This study assessed viral load change, its predictor variables, and the joint association between viral load change and time to death.MethodsAn institution-based retrospective follow-up study was conducted. The data were extracted from 24 April to 30 May 2022 using charts of 489 study participants selected using simple random sampling. OpenBUGS software from the R2OpenBUGS R package was used for model building. A joint Tobit skewed normal mixed effects model and survival analysis using a Bayesian approach was employed.ResultsThe data were extracted from a total of 489 participants. Starting from six months post-treatment initiation (time zero), the log viral load decreased by 0.027 log units per month until 10.82 months of follow-up, while after 20.9 months, it increased by 0.034 log units per month. Participants who took ART medication outside of the catchment health facility had 0.29 log viral load unit higher than within the catchment health facility. The hazard of death was 3.5 times higher for individuals whose log viral load slope increased by one standard deviation from the population slope during the first 10.82 months of follow-up.ConclusionThe change in log viral load increment was high during the latter follow-up period compared to the decrement in log viral load at the beginning of the follow-up period. Duration of treatment, taking ART medication outside the catchment area, baseline WHO stage three and four, poor adherence were associated with log viral load change. Addressing stigma and discrimination is essential to prevent ART patients from seeking treatment outside the catchment area, improve treatment outcomes and reduce viral load rebound.